Tumor grade may be used to select patients with multifocal hepatocellular carcinoma for resection. Issue 7 (July 2020) - Ruff, Samantha M.; Rothermel, Luke D.; Diggs, Laurence P.; Wach, Michael M.; Ayabe, Reed I.; Martin, Sean P.; Boulware, David; Anaya, Daniel; Davis, Jeremy L.; Mullinax, John E.; Hernandez, Jonathan M.
Abstract: Background: While resection is a recommended treatment for patients with stage 1 hepatocellular carcinoma (HCC), it remains controversial for multifocal disease. We sought to identify patients with multifocal HCC with survival after resection similar to patients with clinical stage 1 HCC. Methods: The National Cancer Database was queried to identify patients that underwent resection for HCC. Results: In this study, 2990 patients with a single tumor, and 1087 patients with multifocal disease confined to one lobe underwent resection. In the multifocal cohort, patients with clinical stage 3 (HR 1.54, CI 1.31–1.81, p < 0.0001) or 4 (HR 2.27, CI 1.57–3.29, p < 0.0001) disease, and those with moderately-differentiated (HR 1.32, CI 1.06–1.64, p = 0.012) or poorly differentiated/undifferentiated tumors (HR 1.53, CI 1.20–1.95, p = 0.0006) were associated with worse overall survival (OS). There was no difference in OS between patients with well-differentiated clinical stage 2 multifocal HCC and those with all grades of clinical stage 1 HCC (median of 84.8 (CI 66.3–107.2) vs 76.2 months (CI 71.2–81.3), respectively, p = 0.356). Conclusions: Patients with well-differentiated, clinical stage 2 multifocal HCC confined to one lobe experience similar OS following hepatic resection to patients with clinical stage 1 disease. These findings may impact the management of select patients with multifocal HCC.